Antibacterial Test of Sand Sea Cucumber Extract (Holothuria scabra) Against the Growth of Staphylococcus aureus ATCC 25923 - Carens Sintha Iralin De Ivanka; R.Varidianto Y.T; Suliman Purwoko (Jurnal FARMASIMED (JFM), 2026)
Background: Indonesia is a developing country with a high prevalence of infectious diseases with the most common cause being Staphylococcus aureus  bacteria. Treatment for S.aureus bacterial infection itself uses antibiotics. However, the high number of antibiotic resistance cases in Indonesia is a very important health problem. Indonesia itself is a country with a very wide sea so that a lot of marine wealth is very useful in health. One of them is sand sea cucumber which can help fight bacteria because it contains compounds such as saponins,and alkaloids, triterpenoids which are useful as antibacterials. The aims of the study is to determine the effectiveness of sand cucumber extract (Holothuria scabra) in various concentrations such as 25%, 50%, 75%, and 100% which is addressed through the inhibition zone produced against the growth of S.aureus bacteria. Objective: To determine the antibacterial activity of Sand cucumber extract (Holothuria scabra) by measuring the inhibition zone produced using the disc diffusion method. Method: There were 6 treatment groups in this study 4 of which were treatment groups with concentrations of 25%, 50%, 75%, and 100% and 2 control groups, namely the positive control group (amoxicillin) and the negative control group (sterile distilled water) where each group was repeated 4x. Then the data were analyzed using Kruskal Wallis test and continued with Mann-Whitney U test. Result: The average inhibition zone with a concentration of 25% produced an average inhibition zone of 7.12 mm; 50% concentration of 8.37 mm; 75% concentration had an inhibition of 9.41%, in the 100% treatment group produced an average inhibition zone of 11.68mm, negative control showed no inhibition, and positive control with an average inhibition zone of 16.93 mm.The Kruskal Wallis test showed that there was a significant mean difference between the 6 groups with a significant value of 0.001 (p<0.005). Conclusion: Sand cucumber extract (Holothuria scabra) can inhibit the growth of Staphylococcus aureus  ATCC 25923 bacteria so that it can be used as an alternative medicine or natural antibiotic.